2012
DOI: 10.1002/ps.3349
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol delivery of trail pheromone disrupts the foraging of the red imported fire ant, Solenopsis invicta

Abstract: The feasibility of using aerosol for delivery of trail pheromone was demonstrated, but the need for high purity combined with the difficulty of commercial supply makes this technique impractical. However, the commercial production of Z,E-α-farnesene of high purity by industrial biotechnology or from (E)-nerolidol may be possible in future, which would facilitate further development of trail pheromone disruption of S. invicta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Several investigations also have been undertaken to determine the potential of trail pheromones for managing populations of various pest species. Studies of 2 economically important invasive species, the Argentine ant Linepithema humile (Mayr) (Hymenoptera: Formicidae) (Suckling et al 2008(Suckling et al , 2010a(Suckling et al , 2011Tanaka et al 2009;Nishisue et al 2010) and the red imported fire ant Solenopsis invicta Buren (Hymenoptera: Formicidae) (Suckling 2010b(Suckling , 2012, showed that exposure to synthetic trail pheromone interfered with the ability of the ants to follow their authentic trails, and negatively impacted the insects' foraging behavior. However, there was no indication in these studies that such disruption caused direct mortality, or resulted in a reduction of population size even when the ants were exposed to the synthetic pheromone for the duration of 2 consecutive field seasons (Nishisue et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations also have been undertaken to determine the potential of trail pheromones for managing populations of various pest species. Studies of 2 economically important invasive species, the Argentine ant Linepithema humile (Mayr) (Hymenoptera: Formicidae) (Suckling et al 2008(Suckling et al , 2010a(Suckling et al , 2011Tanaka et al 2009;Nishisue et al 2010) and the red imported fire ant Solenopsis invicta Buren (Hymenoptera: Formicidae) (Suckling 2010b(Suckling , 2012, showed that exposure to synthetic trail pheromone interfered with the ability of the ants to follow their authentic trails, and negatively impacted the insects' foraging behavior. However, there was no indication in these studies that such disruption caused direct mortality, or resulted in a reduction of population size even when the ants were exposed to the synthetic pheromone for the duration of 2 consecutive field seasons (Nishisue et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Future surveillance tools could include multiple species traps, (Vargas et al, 2012;Brockerhoff et al, 2013) or generic floral or other lures to widen the target group (El-Sayed et al, 2008) but innovation is needed in socially-acceptable eradication tactics also. Examples include attempts to develop novel control tactics based on cross species communication disruption between fruit flies (Suckling et al, 2007), release of sterile male Mediterranean fruit flies treated with moth sex pheromone for mating disruption, and trail pheromone disruption of ants (Suckling et al, 2012a;Westermann et al, 2014).…”
Section: Biosecurity Toolkit For Surveillance and Eradicationmentioning
confidence: 99%
“…Lastly, it would be interesting to see if similar substances can be identified for other ant species and these results can be replicated, as for instance has already been shown for the Red Imported Fire ant (Suckling et al 2012). It would also be essential to improve upon the formula of the pheromone by including additional components (Choe et al 2012), to provide complete disruptions with lower concentrations, and optimizing the delivery mechanism to allow an easier, yet similarly resistant to water and wind, deployment of the pheromone.…”
Section: Constraints and Further Researchmentioning
confidence: 71%
“…For example, in Monomorium pharaonis, it has been shown that negative trail pheromone communicates a 'no entry' signal to workers, leading them to turn back on the current trail (Robinson et al 2005). For the Red Important Fire Ant, aerosol application of its trail pheromone Z,E-α-farnesene has reduced arrival success of workers following trails, as well as trail integrity (Suckling et al 2012). Therefore, specific trail pheromones, if applied on a large scale, may offer management opportunities for specific invasive ant species.…”
Section: Pheromone Based Management Techniques For Invasive Speciesmentioning
confidence: 99%